Silicon isotope separation by two frequency IRMPD - Risaro, Matías Ariel (2017)
InfraRed Multi-Photon Dissociation (IRMPD) is a highly selective laser isotope separation technique. This process consists of a sequential IR photon absorption from the ground vibrational state up to dissociation by a molecule that contains the isotope of interest. High dissociation threshold molecules require large intensity radiation fields. This drawback could be overcome by two-frequency IRMPD. In this technique, a low energy laser resonant with the first energy levels guarantees isotopic selectivity excitation and a second non-resonant large energy laser achieves molecular dissociation. The possibility of obtaining silicon laser isotopic enrichment using SiF4 as working molecule was investigated in this work. Two-frequency IRMPD of SiF4 with two TEA CO2 single transverse mode lasers was studied in a molecular jet. The dissociation process was monitored with a Time-of-Flight mass spectrometer with UV multi-photon ionization. The excitation laser fluence and wavelength dependence of the isotopic dissociation estimator, α, and the enrichment factor estimator, β, were determined and compared to those obtained in single-frequency IRMPD.